Approaches to Repair of Penetrating Injuries of the Proximal, Mid, and Distal Esophagus. Issue 3 (March 2022) - Castater, Christine; Nguyen, Jonathan; Perez, Matthew; Butler, Caroline; Meyer, Courtney; Todd, Samuel Rob; Sciarretta, Jason; Smith, Randi; Archer-Arroyo, Krystal; Grant, April
Introduction: Traumatic esophageal injuries represent less than 10% of traumatic injuries. Penetrating injuries represent an even smaller but more lethal percent. Esophageal injuries can be cervical, thoracic, or abdominal with decreasing frequency. Cervical and thoracic esophageal injuries represent >80% of these injuries and are more morbid. Morbidity and mortality are increased with delayed identification. Although diagnosis can be hard, management is similar despite location. Cases: We present 3 cases of esophageal injuries to the cervical, thoracic, and abdominal esophageal segments with descriptions on diagnosis, repair, and management differences Discussion: Despite low incidence of penetrating esophageal injuries, morbidity and mortality are extremely high, especially with associated injuries. Early identification and treatment is paramount. Anatomical knowledge is necessary for successful surgical management. Primary repair in 2 layers should be attempted whenever possible including musical closure with absorbable suture. Flaps, diversions, wide drainage, and feeding tube access should always be key surgical considerations. Flaps can include sternocleidomastoid muscle for cervical injuries, intercostal muscle, diaphragm, and pericardium for thoracic injuries and "Thal" gastric flaps for gastroesophageal junction and abdominal injuries. Successful identification and management can lead to increased survival